Perceived Workplace Incivility among Employees of Faith-Based Firms: The Predictive Role of Emotional Stability and Ethical-Moral Standard - Okpala, Micheal O; Okoli, Paul C; Ofojebe, Chukwuma P; Nweke, Kingsley O; Iwudo, Martin C (Practicum Psychologia, 2020)
Workplace incivility is not healthy for both the employers and the employees. Literature search revealed gap in knowledge on the predictive role of emotional stability and ethical-moral standard on perceived workplace incivility. To fill this gap and contribute in obtaining veritable solution to workplace incivility, present study extends the literature on workplace incivility by investigating perceived workplace incivility: the predictive role of emotional stability and ethical-moral standard. Participants were 133 employees (51 males and 82 females) of faith-based firms in Anambra State, selected through the use of total population sampling technique. Their ages ranged from 24 years to 47 years, with a mean age of 35.50 and a standard deviation of 2.18. Workplace Incivility Scale (WIS), Emotional Stability Scale (ESS), and Ethical-Moral Self Inventory (EMSI) were used for data collection. Two hypotheses were tested using multiple regression statistic. Result revealed that only ethical-moral standard significantly and positively predicted workplace incivility at β = .173, p<.05, (n = 133), while emotional stability did not, β = -.007, p>.05, (n = 133). Following these findings, it was recommended that faith-based business owners should be very conscious of how they talk down or neglect the contributions their employees are making. Such omissions could be among what their employees perceive as workplace incivility.